IMPROVING DISTRIBUTION CHANNEL AT PT. SUMBER GRAHA SEJAHTERA (SGS) - Firdaus Alamsjah; Aryo Adityo Wirawan; Saleh Sendiko (Journal of Business Strategy and Execution, 2011)
SGS is the company is a leading timber processing company in Indonesia. With over 1 million m³ of processing capacity, they are among the top five tropical hardwood plywood producers globally, and one of the largest in Indonesia. The purpose of this research is to develop SGS distribution network especially related to the company’s intermediaries.  Through their owned network, the company hopes that it will create brand loyalty and also create integrated services for consumers which most of company’s consumers are developer and contractor where they are became company’s target market. In order to reach maximum result it is better for the company to replace current distribution channel and build new distribution channel. The first step in designing distribution channel, the company must understand the service output levels its target consumers want. The second step is establishing objectives and constraint for the channel. The third step is identifying and evaluating major channel alternatives. Therefore, to build new distribution strategy aim to retain all control to the market as a key factor, writers provide three alternatives of distribution channel strategy to the company. All the alternative of distribution strategy are made based on the company’s sales data which is provide information about the company sales areas as well as total sales volume on each area. To increase company’s sales, one of the strategies that company could implement to increase sales is developing suitable and sophisticated distribution channel. Meanwhile, to develop suitable distribution channel, the company should knows well about the market specifically about their consumers.